Incidence of and risk indicators for vasa praevia: a systematic review. (23rd December 2015) - Ruiter, L; Kok, N; Limpens, J; Derks, JB; de Graaf, IM; Mol, BWJ; Pajkrt, E
Abstract : Background: Vasa praevia (VP) is a rare phenomenon that is assumed to increase the risk of severe complications, including fetal death. Critical data on its incidence are lacking, so there is no rational basis for prenatal screening. Objectives: To review the literature on the incidence and risk indicators for VP. Search strategy: We searched OVID MEDLINE, OVID EMBASE, the Cochrane Library and PubMed for case–control and cohort studies on incidence and risk indicators for VP. Selection criteria: Two reviewers selected studies and scored their methodological quality. Data collection and analysis: We calculated the mean incidence of VP. We constructed 2 × 2 tables cross‐classifying potential risk indicators against the incidence of VP to calculate common odds ratios and 95% confidence intervals, using the Mantel–Haenszel method. Main results: We included 13 studies (two prospective cohort studies, ten retrospective cohort studies and one case–control study) reporting on 569 410 patients with 325 cases of VP. Based on ten included cohort studies providing information on the incidence, the mean incidence of VP was 0.60 per 1000 pregnancies. We identified five different risk indicators and markers for VP: second‐trimester placenta praevia, conception by assisted reproductive technologies, a bilobed or succenturiate placenta, umbilical cord insertion in the lower third part of the uterus at first‐trimester ultrasound and velamentous cord insertion. Almost 83% of the cases of VP had one or more risk indicators. Authors' conclusions: In view of the low incidence, screening for VP in an unselected population is not advised. Targeted screening of women with one or more risk indicators as a part of routine mid‐gestation scanning should be considered. Tweetable abstract: Vasa praevia is more common in placenta praevia, conception by ART, velamentous cord insertion and bilobed placenta. Tweetable abstract: Vasa praevia is more common in placenta praevia, conception by ART, velamentous cord insertion and bilobed placenta. This article includes an audio podcast in which author, Dr Ruiter discusses this paper with Emeritus Editor, Prof Steer available athttps://soundcloud.com/bjog/author-interview-vasa-praevia